2021
DOI: 10.48550/arxiv.2111.08337
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lens parameters for Gaia18cbf -- a long gravitational microlensing event in the Galactic plane

Katarzyna Kruszyńska,
Ł. Wyrzykowski,
K. A. Rybicki
et al.

Abstract: Context. The size of the Einstein Radius in a microlensing event scales as a square root of the mass of the lens. Therefore, long-lasting microlensing events are the best candidates for massive lenses, including black holes. Aims. Here we present the analysis of the Gaia18cbf microlensing event reported by the Gaia Science Alerts system. It has exhibited a long timescale and features characteristic to the annual microlensing parallax effect. We deduce the parameters of the lens based on the derived best fittin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Wyrzykowski et al 2016;Wyrzykowski & Mandel 2020;Golovich et al 2020). For example, the parallax lensing event Gaia18cbf has been recently analysed by Kruszyńska et al (2021), who found three possible solutions using Gaia data alone, and two possible solutions with follow-up. In most studies (Wyrzykowski et al 2016;Wyrzykowski & Mandel 2020;Kruszyńska et al 2021), the modes of the posterior are sampled and analysed separately, yielding alternative solutions for lens mass and distance.…”
Section: Light Curve Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…Wyrzykowski et al 2016;Wyrzykowski & Mandel 2020;Golovich et al 2020). For example, the parallax lensing event Gaia18cbf has been recently analysed by Kruszyńska et al (2021), who found three possible solutions using Gaia data alone, and two possible solutions with follow-up. In most studies (Wyrzykowski et al 2016;Wyrzykowski & Mandel 2020;Kruszyńska et al 2021), the modes of the posterior are sampled and analysed separately, yielding alternative solutions for lens mass and distance.…”
Section: Light Curve Modellingmentioning
confidence: 99%
“…For example, the parallax lensing event Gaia18cbf has been recently analysed by Kruszyńska et al (2021), who found three possible solutions using Gaia data alone, and two possible solutions with follow-up. In most studies (Wyrzykowski et al 2016;Wyrzykowski & Mandel 2020;Kruszyńska et al 2021), the modes of the posterior are sampled and analysed separately, yielding alternative solutions for lens mass and distance. A possible disadvantage is not returning the relative probability of those solutions and only using 𝜒 2 as an indicator of weak preference towards one of the solutions.…”
Section: Light Curve Modellingmentioning
confidence: 99%
See 1 more Smart Citation